2017
DOI: 10.1177/1049732317743238
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of Faith Community Nurse–Led Cognitive-Behavioral and Spiritual Counseling for Dementia Caregivers

Abstract: This article presents themes emerging from semistructured interviews with dementia family caregivers in rural communities who participated in an integrative, cognitive-behavioral and spiritual counseling intervention, and with faith community nurses (FCNs) who delivered the intervention. The primary objectives of the counseling intervention were to ameliorate dementia caregivers' depressive affect and the severity of their self-identified caregiving and self-care problems. The qualitative portion of the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 68 publications
1
13
0
1
Order By: Relevance
“…[20] In a qualitative study on family carers of dementia people, spirituality has also been identified as the main factor that can ameliorate depressive symptoms in the caregivers. [38] These studies are consistent with our findings emphasizing the potential effects of spirituality via SCSs to improve psychological status in the caregivers.…”
Section: Discussionsupporting
confidence: 92%
“…[20] In a qualitative study on family carers of dementia people, spirituality has also been identified as the main factor that can ameliorate depressive symptoms in the caregivers. [38] These studies are consistent with our findings emphasizing the potential effects of spirituality via SCSs to improve psychological status in the caregivers.…”
Section: Discussionsupporting
confidence: 92%
“…For the most part, all 14 qualitative studies meet the quality criteria for appropriateness of the methods and reporting of the data collection methods and sources (Devido et al, 2018; Dyess, 2008; Dyess & Chase, 2012; Grebeldinger & Buckley, 2016; Kazmer et al, 2017; King, 2011; Millerd, 2010; Mock, 2017; Newbanks & Rieg, 2011; Sheehan et al, 2013; Shores, 2014; Van Dover & Pfeiffer, 2011; Young, 2015; Ziebarth & Miller, 2010). According to MMAT criteria, there is insufficient evidence to confirm that the findings are adequately derived from the data in six of the 14 studies; we appraised this criterion as “can't tell” in five articles (Grebeldinger & Buckley, 2016; King, 2011; Mock, 2017; Sheehan et al, 2013; Young, 2015) and “no” in one study (Newbanks & Rieg, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…For example, one high-quality study (Losada et al, 2015) indicated that both face-to-face counselling interventions (CBT and commitment therapy) were superior in reducing depressive symptoms compared to the control group (a two-hour dementia psycho-educational workshop and booklet termed 'minimal support') post-intervention. Similarly, a high-quality study (Kazmer et al, 2018) indicated cognitive-behavioural counselling can improve care-giver depression. Furthermore, two case studies delivered cognitive-based counselling interventions face-to-face to care-givers (Jimenez and Gray, 2006;Hamill and Mahony, 2011), and reported that depression and anxiety scores were reduced.…”
Section: Psychotherapy/counselling Studiesmentioning
confidence: 99%
“…Within the 11 studies that adopted a cognitive-behavioural/cognitive-analytic approach, only three studies delivered the intervention face-to-face (Jimenez and Gray, 2006;Losada et al, 2015;Kazmer et al, 2018), to a range of sample sizes (N = 1, 7 and 135 respectively).…”
Section: Psychotherapy/counselling Studiesmentioning
confidence: 99%